Stress analysis of a single prosthesis on a poorly positioned implant - Reis, Francisco Carlos dos Santos (2021)
The mechanical positioning behavior of a mal-positioned implant was evaluated in the finite element method. Models were created in SolidWorks Professional 2013® software with a single implant rehabilitation. The following were analyzed: Control Group, crown aligned to the implant long axis; Experimental Group, crown shifted 3 mm mesial proximally to the implant axis. Compressive stresses in cortical and medullary bone, and Von Mises stresses in implants and components were evaluated. With 100 N occlusal loading at 5 points. The peak von Mises stresses in the prosthetic screw of the experimental group (138.45 MPa) were 43.60% higher compared to the control group (96.41 MPa). The stresses in the prosthetic pillar were localized in the abutment region and the experimental group showed (875.63 MPa), 28% higher than the control group (683.88 MPa). Regarding the implant, the maximum stress peaks were located in the implant platform and the experimental group showed stress values of (1081.4) MPa and was 26.42% higher than the control 855.39 MPa. The cortical bone tissue of the experimental group showed shear stress values 10.81% higher than the control. The stress values were 151.36 MPa for the experimental group and (136.59 Mpa) for the control. The medullary bone showed shear stress (8.31 MPa) and was 12.29% higher than the control (7.40 MPa). A maximum peak was obtained in the cervical region of the medullary bone, adjacent to the cortical bone. The experimental group with a mal-positioned implant showed the highest maximum stresses for all simulated prosthetic components.